2023
DOI: 10.3390/bios13050517
|View full text |Cite
|
Sign up to set email alerts
|

On-Chip Nucleic Acid Purification Followed by ddPCR for SARS-CoV-2 Detection

Abstract: We developed a microfluidic chip integrated with nucleic acid purification and droplet-based digital polymerase chain reaction (ddPCR) modules to realize a ‘sample-in, result-out’ infectious virus diagnosis. The whole process involved pulling magnetic beads through drops in an oil-enclosed environment. The purified nucleic acids were dispensed into microdroplets by a concentric-ring, oil–water-mixing, flow-focusing droplets generator driven under negative pressure conditions. Microdroplets were generated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Following the individual droplet analysis, the target gene fragment-containing droplets are given the labels 1 and 0, and when paired with the Poisson distribution, the specific target gene fragments are determined. 18 For “in-sample, out-of-result” infectious virus diagnostics, Ma Cong et al 19 developed microfluidic chips coupled with nucleic acid purification and ddPCR modules. Throughout the entire procedure, magnetic beads were pulled through the oil-enclosed droplets.…”
Section: Droplet Microfluidicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the individual droplet analysis, the target gene fragment-containing droplets are given the labels 1 and 0, and when paired with the Poisson distribution, the specific target gene fragments are determined. 18 For “in-sample, out-of-result” infectious virus diagnostics, Ma Cong et al 19 developed microfluidic chips coupled with nucleic acid purification and ddPCR modules. Throughout the entire procedure, magnetic beads were pulled through the oil-enclosed droplets.…”
Section: Droplet Microfluidicsmentioning
confidence: 99%
“…A concentric ring, oil–water mixing, and flow-focused droplet generator are used to disperse purified nucleic acids into microdroplets while being powered by negative pressure. 19 Chen, Liao et al have also reported a ddPCR platform that achieves high sensitivity and rapidity without the need for bulky laboratory equipment. 20…”
Section: Droplet Microfluidicsmentioning
confidence: 99%
“…Based on the insolubility between oil and water, droplet dNAA (ddNAA) is one of the dNAA methods that disperses sample solutions into micro-droplets in an oil phase fluid, using microfluidic approaches such as flow focusing, coaxial flow, step emulsification, ink-jetting, ultrasound excitation, oscillating, etc. [4][5][6][7][8][9]. For a certain volume of sample Biosensors 2023, 13, 888 2 of 12 solution, generating droplets with smaller sizes means larger numbers of droplets would be obtained, which leads to a higher detection sensibility.…”
Section: Introductionmentioning
confidence: 99%